A flawed portrait. The image of Zofia Kossak in the accounts of former Birkenau female internees - Kowalska-Leder, Justyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article indicates how the figure of Zofia Kossak has been recorded in the unpublished accounts by former KL Auschwitz-Birkenau female internees who during their internment came into contact with the famous writer and activist of the Polish Underground State. Their testimonies diverge from the hagiographic tone which has dominated the known stories of Kossak’s camp experiences, rather resembling Tadeusz Borowski’s infamous post-WWII article entitled Alicja w krainie czarów.